FUNGSI OBJEK WISATA TELUK KENDARI BEACH DALAM MEMENUHI KESEJAHTERAAN PELAKU USAHA KECIL MIKRO DI KOTA KENDARI - Faana, Afil; Sarmadan, Sarmadan; Tanzil, Tanzil (Universitas Halu Oleo, 2022)
Micro Enterprises are productive businesses owned by individuals or small-scale individual businesses that are traditional and informal to earn income and meet the welfare of both individuals and families. The purpose of this study is to find out how the function of the Kendari Beach Bay tourist attraction in meeting the welfare of small and micro business actors. This research method is descriptive qualitative, determination of informants using purposive techniques, data collection through literature study, observation, interviews and documentation, data analysis by means of data reduction, data presentation and drawing conclusions. The results of the study show that first, providing employment / providing business opportunities for small and micro business actors to open businesses in the Kendari Beach bay tourist attraction area. Second, it is able to increase income. The existence of a tour can help micro-entrepreneurs to be able to provide them with a better income compared to when they do business not at tourist sites. Third, able to improve the standard of living / quality of life. The existence of the Kendari Beach Bay tourist attraction is able to provide good access for small and micro business actors to be able to improve the quality of their standard of living in terms of meeting primary needs, namely the need for clothing, food and housing as well as fulfilling secondary needs quite well.